A formação musical de professores em cursos de Pedagogia: um estudo das universidades públicas do RS - Furquim, Alexandra Silva dos Santos (2009)
The present research was developed in the course of Master in Education, in the Federal University of Santa Maria/RS, in the line of research Education and Arts and it is related to the training group named Action and Research in Music Education (FAPEM). The study aimed at investigating the Music Education in teacher training courses in education, offered during the day and in the presence mode, the public universities of the RS. Specifically, it is intended to understand the Political Pedagogical Project (PPP) of courses in pedagogy and the proposals contained therein for Music Education and developed courses in pedagogy and understand how the Music Education is articulated with the general education teacher of the early years of schooling. The reasons for the study is based on authors of teacher training (NÓVOA, 1995; GARCIA, 1999; DINIZ-PEREIRA, 2008; MIZUKAMI, 2008), the pedagogy course (BRZEZINSKI, 1999; 2008; SILVA, 1999; SAVIANI, 2008; SCHEIBE, 2008) and Music Education in Pedagogy (BELLOCHIO, 2000; 2001; 2004; 2008; FIGUEIREDO, 2001; 2003b; 2004; 2007), among others.The study has a qualitative approach, characterized as a multiple case study (YIN, 2005). Data collection was conducted through document analysis of the PPP and programs of the disciplines of Art/Music which are part of the syllabus of the courses in pedagogy. It also involved semi-structured interviews with five teachers and four coordinators of the courses of education of universities participating in the study. Therefore, the data were analyzed according to the technique of content analysis (BARDIN, 1977). In order to know the PPP of the courses of education, it was observed that all the institutions are designed to train graduates in education and it has the training for teaching in the early years of schooling as a focus. Specifically with regard to Music Education in academic and professional training in pedagogy, it was found that the area of music in the syllabus of the course of education in two universities is considered a specific discipline. In other institutions, the area of music it is not a a specific discipline in their syllabus. In two universities there is a discipline that focuses on the art, but the Music Education is not the proposal of the discipline. In another institution, the area of Music is part of a discipline of art, but the emphasis lies in the knowledge inherent in the Visual Arts. It is believed that knowing the course of training in music education is one way of fostering further discussions, actions and proposals in order to resize the role and the education of the multiple subject teacher about Music Education school.